Engineering metal–metal oxide surfaces for high-performance oxygen reduction on Ag–Mn electrocatalysts. Issue 4 (10th March 2022) - Zamora Zeledón, José A.; Gunasooriya, G. T. Kasun Kalhara; Kamat, Gaurav A.; Kreider, Melissa E.; Ben-Naim, Micha; Hubert, McKenzie A.; Avilés Acosta, Jaime E.; Nørskov, Jens K.; Stevens, Michaela Burke; Jaramillo, Thomas F.
Abstract : Diverse Ag–MnO x surface sites/structures in Ag–Mn electrocatalysts afford robust local electronic structures tuned for efficient oxygen reduction. Abstract : Understanding fundamental material–property relationships in mixed-element catalyst systems is crucial to advancing the viability of renewable electrochemical energy technologies, an important part of creating a more sustainable future. Herein, we report our insight on the nature and dynamics of highly active silver–manganese oxide (Ag–MnO x ) catalyst surfaces for the oxygen reduction reaction (ORR) via a combined experimental–theoretical approach. Experimentally, we synthesize well-mixed Ag–Mn co-deposited thin films that are measurably flat and smooth, despite Mn surface migration and oxidation upon air exposure and electrochemical measurements. Cyclic voltammetry in 0.1 M KOH demonstrates up to 10-fold specific activity enhancements over pure Ag at 0.8 V vs. RHE for Ag-rich films (70–95% Ag in bulk). To further understand the Ag–Mn system, separate samples were synthesized with small amounts of Mn sequentially deposited onto the surface of a pure Ag thin film (Mn@Ag), ranging from partial to full surface coverage (down to 0.3 nmMn cm−2geo ∼ 0.2 μgMn cm−2geo). These sequentially deposited Mn@Ag films show analogous performance to their co-deposited counterparts indicating similar enhanced active sites. With density functional theory (DFT), we calculate that this enhancement arises from the tuned d-band of these material surfaces owing to the optimal hybridization of the electronic structures in specific Ag and MnO x geometries. Together, electrochemical measurements, DFT calculations, X-ray absorption spectroscopy, and valence-band X-ray photoelectron spectroscopy suggest synergistic electronic interactions between Ag and MnO x yield enhanced oxygen adsorption, and thus ORR activity, with DFT highlighting the Ag–MnO x interface sites as the most enhanced. This work demonstrates how combined experimental–theoretical methods can help design electrocatalysts with enhanced electrocatalytic properties and understand the nature of complex mixed metal–metal oxide surfaces.